2020
DOI: 10.5551/jat.49833
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Associated Factors of Sudden Death in Patients on Hemodialysis: 10-Year Outcome of the Q-Cohort Study

Abstract: The incidence of sudden death and its risk factors in patients on hemodialysis remain unclear. This study aimed to clarify the incidence of sudden death and its risk factors in Japanese patients on hemodialysis. Methods: A total of 3505 patients on hemodialysis aged ≥ 18 years were followed for 10 years. Multivariateadjusted hazard ratio (HR) with 95% confidence interval (95% CI) of each risk factor of sudden death were calculated using a Cox proportional hazards model. Results: During the 10-year follow-up, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
(61 reference statements)
0
23
1
Order By: Relevance
“…Due to the limited number of outcomes of this relatively small cohort, organ-specific and etiology-specific interpretations of the results were difficult. Sixth, although some cohort studies reported a long-term follow-up for 10 years in hemodialysis patients 33) , our cohort was followed up for only 5 years. A longer follow-up period merits a larger number of outcomes, whereas it would analyze the association of the exposure with remote outcomes.…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosismentioning
confidence: 98%
“…Due to the limited number of outcomes of this relatively small cohort, organ-specific and etiology-specific interpretations of the results were difficult. Sixth, although some cohort studies reported a long-term follow-up for 10 years in hemodialysis patients 33) , our cohort was followed up for only 5 years. A longer follow-up period merits a larger number of outcomes, whereas it would analyze the association of the exposure with remote outcomes.…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosismentioning
confidence: 98%
“…In HD patients, SD could be induced by various factors such as the presence or history of cardiovascular disease, the problem of fluid volume, electrolyte disorder, and sympathetic overactivity [ 23 ]. Thus, the onset of SD is determined to be most common in the first year or approximately 10 years after HD initiation [ 3 , 24 ]. The increased SD rate would be due to the increased volume and potassium accumulated over a longer weekend interval [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sudden death (SD) is considered a common occurrence in patients undergoing hemodialysis (HD) [ 1 ]. Recent studies show that 13–16% of all deaths in Japanese HD patients were due to SD [ 2 , 3 ]; this indicates that SD is now more common even in the Japanese dialysis clinical setting than previously believed [ 4 ]. HD patients are determined to be at an increased risk for SD due to several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic kidney disease (CKD) and/ or those on dialysis therapy have multiple risk factors for CVD 74,75) ; thus, it is critical to predict and prevent CVD by making use of surrogate markers 76,77) . There are several reports regarding stiffness parameter in patients with CKD and/or those undergoing hemodialysis.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%